Memória emblemática: o que os tradicionais nos contam sobre seu passado? - ÁLVARO, Maria Ângela Gemaque (Universidade Federal do Pará, 2012)
This work discusses the importance of family tradition on constructing social representations that are incorporated into a classification system used in a given context. Memory of two family groups considered to be traditional in the city of Belém are analyzed, these groups being so considered in virtue of an exceptional historic trajectory. The central conducting element in such a discussion is social memory, with emphasis on the way it is considered in the studies by Maurice Halbwachs. Upon the exam of oral and written narratives, the study goes on incorporating the themes of tradition, family and history, and developing two main points: 1) How the adjective traditional is constructed and attributed to some families? This question is approached by using the concept of “invented tradition”, and by relating the mnemonic construction of such groups to processes of consecration of family names, and to status authentication. 2) How the involving society has been convinced to accept that image? Emphasis is given on the ideological aspects of kinship and history.